Penggunaan Model “Angkat Bloe” dalam Wakaf Produktif: Justifikasi dan Hambatan (Waqf Productive Using “Angkat Bloe” Model: the Rationales and Obstacles) - Fithriady Fithriady; Azharsyah Ibrahim (Sharia and Law Faculty, 2017)
Waqf is one of the instruments in Islamic economics to boost up the economic justice and welfare of society. Indonesia, as the largest Muslim country in the world, has the potency to utilize this sector. Per 2012, according to Ministry of Religious Affairs, there are 3.49 billion square meters of land waqf spreading in 420.003 locations all around Indonesia. If these numbers were converted into cash, it surely will result in a fantastic number. However, most of these lands were still unproductive (idle) as most of them are only used for building mosques, schools, funerals, and other unproductive buildings. In some provinces in Indonesia, like Aceh, the used of asset waqf other than what it was literally stated by the giver is prohibited. The rules were set by traditional religious clerics with very rigid interpretations. Consequently, it creates mindset of its people that waqf should be treated in such a rigid way although they knew it could be used for a bigger purpose and get bigger maslahah for the whole ummah. To change the mindset is not easy as it has been ongoing for generations. One of the way is by inserting the local value and approach into management waqf. In Aceh, there were many models of muamalah that have been practicing and living in the society for such a long time. Among many, Angkat Bloe model is seen suitable to be inserted into management waqf. Angkat Bloe is a kind of contract that is commonly used in trading activities for the purpose of the asset that has been sold to be returned. Prior transaction, the seller and buyer set an agreement that the asset will be sold back to the seller after the buyer operate it for certain times at the same price as it was sold. Based on the above explanation, this paper will try to put an effort in providing solutions by inserting the local model into management waqf. The model will be justified using Quranic verses and related hadiths, the concept of maslahah, the view of ulama. The rationales and possible obstacles will also be highlighted.